Advances ECCIP Project: Study of climate change and its impact on Peru - Zuta, Salvador (1999)
The advance in the analysis of oceanographic and meteorological conditions for the period 1988-1996 is presented, with special emphansis on the ENSO phenomenom, which has as its main scenary the Tropical Pacific, with spectacular manifestations taking place in the Peruvian area. The products of research and observational programmes carried out by national institutions and international organizations are the basic basic reference information, being the key variables the sea surface temperature, oceanic currents, sea level variations, surface winds, atmospheric pressure at sea level and precipitation. It is establised that the moderate ENSO 1991-93 and the moderate cold period 1995-96, by the moderate and longer ENSO 1991-93 and the moderate cold period a995-96, and in the short term a new warm episode is expected. This possibility urges us to be prepared with a National Programme on Climate Variability (CLIVAR) in order to assure the sustainable development of this country.